ANALISIS KEMAMPUAN MANAJERIAL DOSEN DENGAN PRESTASI BELAJAR MAHASISWA - Larasati, Sri (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2014)
This research aims to investigate the influence of the lecturers’ conceptual skill, the lecturers’ interpersonal skill, and the lecturers’ technical skill on the students’ learning achievement. The sample was the students of Administration Hotel program study. The result of t-test using SPSS 17 for all of independent variables (conceptual skill= 0.000, interpersonal skill= 0.001, and technical skill= 0.044) showed that the hypothesis 1 was proven. It means that the lecturers’ conceptual skill, interpersonal skill, and technical skill influenced the students’ learning achievement. The result of t-test was supported by the result of F-test which was very significant (=0.000). The influence of the independent variables (X) on the dependent variable (Y) was 68.7%. The result of t-test showed that the hypothesis 2, where the lecturers’ conceptual skill influenced the students’ learning achievement significantly, was also proven. Keywords: conceptual skill, interpersonal skill, technical skill, learning achievement.